Small-molecule compounds inhibiting S-phase kinase-associated protein 2: A review - Jing, Jia; Rui, Li; Junyuan, Sun; Jinfeng, Yang; Zhihao, Hong; Weiguo, Lu; Zhenyu, Jia (Frontiers in Pharmacology, 2023)
S-phase kinase-associated protein 2 (Skp2) is a substrate-specific adaptor in Skp1-CUL1-ROC1-F-box (Lyapina et al.) E3 ubiquitin ligases and widely regarded as an oncogene. Therefore, Skp2 has remained as an active anticancer research topic since its discovery. Accordingly, the structure of Skp2 has been solved and numerous Skp2 inhibiting compounds have been identified. In this review, we would describe the structural features of Skp2 and introduce the ubiquitination function of SCFSkp2, and also summarize the diverse natural and synthetic Skp2 inhibiting compounds reported to date. The IC50 data of the Skp2 inhibitors or inhibiting compounds in various kinds of tumors at cellular levels implied that the cancer type, stage and pathological mechanisms should be taken into consideration when selecting Skp2-inhibiting compound for cancer treatment.